2023
DOI: 10.1186/s12957-023-03091-w
|View full text |Cite
|
Sign up to set email alerts
|

Persistent descending mesocolon as a vital risk factor for anastomotic failure and prolonged operative time for sigmoid colon and rectal cancers

Abstract: Background The diagnostic criteria and effect of persistent descending mesocolon (PDM) on sigmoid and rectal cancers (SRCs) remain controversial. This study aims to clarify PDM patients' radiological features and short-term surgical results. Method From January 2020 to December 2021, radiological imaging data from 845 consecutive patients were retrospectively analyzed using multiplanar reconstruction (MRP) and maximum intensity projection (MIP). PD… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…This contributes to a higher incidence of marginal vascular arch injuries and weaker blood supply at the proximal end of the. Despite our patient being an 18-year-old adolescent, the measured distances (21 mm and 24 mm) were shorter than reported averages (27 mm and 35 mm) [6], likely contributing to her postoperative stenosis, requiring reoperation. The potential use of intraoperative indocyanine green (ICG) to ensure adequate blood supply during the operation is emphasized.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…This contributes to a higher incidence of marginal vascular arch injuries and weaker blood supply at the proximal end of the. Despite our patient being an 18-year-old adolescent, the measured distances (21 mm and 24 mm) were shorter than reported averages (27 mm and 35 mm) [6], likely contributing to her postoperative stenosis, requiring reoperation. The potential use of intraoperative indocyanine green (ICG) to ensure adequate blood supply during the operation is emphasized.…”
Section: Discussioncontrasting
confidence: 74%
“…PDM is confirmed when the descending colon is located medially to the left renal hilum [ 4 ]. Although often asymptomatic, recent studies have identified specific complications associated with PDM, including primary colonic varices [ 14 ], sigmoid colon volvulus [ 15 ], prolonged operative time, anastomotic failure [ 6 ], and postoperative anastomotic stenosis in left-sided colon cancer [ 16 ]. The increased risk of anastomotic failure in PDM cases is linked to the incompletely expanded mesentery of the descending and sigmoid colon, resulting in a shorter length between the inferior mesenteric artery (IMA) and the marginal artery and colon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most PDM cases, LCAs were far from the IMA root or absent. If surgeons are not aware of the anatomical variants of the colonic vessels before surgery, they may easily mistake the marginal vessels for the LCA and injure them during surgery, resulting in ischemia of the descending colon or even an unexpected colostomy [30].…”
Section: Discussionmentioning
confidence: 99%